2020
DOI: 10.1007/s00127-019-01826-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity, reliability, acceptability, and utility of the Social Inclusion Questionnaire User Experience (SInQUE): a clinical tool to facilitate social inclusion amongst people with severe mental health problems

Abstract: Background Individuals with severe mental health problems are at risk of social exclusion, which may complicate their recovery. Mental health and social care staff have, until now, had no valid or reliable way of assessing their clients' social inclusion. The Social Inclusion Questionnaire User Experience (SInQUE) was developed to address this. It assesses five domains: social integration; productivity; consumption; access to services; and political engagement, in the year prior to first psychiatric admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…This study is a secondary analysis based on data collected from The Social Inclusion Questionnaire User Experience (SInQUE) project, a nationally funded research study (Mezey et al, 2020). The SInQUE measure (Mezey et al, 2013) assesses social inclusion across five domains: social integration; productivity; consumption; access to services; and political engagement.…”
Section: Methodsmentioning
confidence: 99%
“…This study is a secondary analysis based on data collected from The Social Inclusion Questionnaire User Experience (SInQUE) project, a nationally funded research study (Mezey et al, 2020). The SInQUE measure (Mezey et al, 2013) assesses social inclusion across five domains: social integration; productivity; consumption; access to services; and political engagement.…”
Section: Methodsmentioning
confidence: 99%
“…As the F-SIM16 was developed in response to an identified need for appropriate measures of social inclusion, so too were other measures, including the SIS (Stickley and Shaw, 2006;Lloyd et al, 2008;Dorer et al, 2009;Secker et al, 2009;Marino-Francis and Worrall-Davies, 2010;Huxley et al, 2012;Mezey et al, 2013). As per the F-SIM16, the development and evaluation of some of these measures have progressed (Huxley et al, 2015;Wilson and Secker, 2015;Mezey et al, 2020), yet none have reported a complete psychometric evaluation to date. Additional limitations include poor generalisability as a result of having been developed for use in specific settings (Stickley and Shaw, 2006;Dorer et al, 2009;Secker et al, 2009;Marino-Francis and Worrall-Davies, 2010) and imbalances in the inclusion of objective/subjective elements (either a greater focus on subjective measures [Stickley and Shaw, 2006;Lloyd et al, 2008;Secker et al, 2009;Marino-Francis and Worrall-Davies, 2010), or an entire focus on objective measures (Dorer et al, 2009)].…”
Section: Other Measures Of Social Inclusionmentioning
confidence: 99%
“…The sample size for this study was dictated by the requirements of the psychometric testing reported by Mezey et al (2020). However, power analysis using Dunlap et al (2004) guided our selection of independent variables for the regression modelling.…”
Section: Sample Size and Powermentioning
confidence: 99%
“…The Social Inclusion Questionnaire User Experience (SInQUE) was developed by the authors to assess social inclusion across five domains; consumption, production, access to services, social integration and civil engagement (Mezey et al, 2020(Mezey et al, , 2013. The higher the score, the greater the level of social inclusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation